2019
DOI: 10.15298/invertzool.16.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in a Pleuroxus aduncus (Jurine, 1820) population (Crustacea: Cladocera: Chydoridae)

Abstract: The morphological variation in a population of Pleuroxus aduncus (Jurine, 1820) from a well in Germany is described. The number of denticles at the postero-ventral corner of the valve are more numerous than normal and abnormalities occur regularly. The observations are discussed in the context of the described variation in number of posteroventral denticles of this species and the causes given for abnormalities in recent literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…There are several causes of abnormalities in cladocerans suggested in the literature. These include toxic substances [11,14,17,19] , eutrophication [18] , and extreme environments [15,20] . De Melo et al (2017) [18] observed abnormalities in Bosmina intestines, which were probably due to the eutrophication of the reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several causes of abnormalities in cladocerans suggested in the literature. These include toxic substances [11,14,17,19] , eutrophication [18] , and extreme environments [15,20] . De Melo et al (2017) [18] observed abnormalities in Bosmina intestines, which were probably due to the eutrophication of the reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…The description of Lynceus longirostris is very brief and there is wide morphological variation in Bosmina longirostris (Müller, 1785) [5] . Several European species are described: B. cornuta (Jurine, 1820) [20] ; B. brevicornis Hellich, 1877; B. brevirostris Fischer, 1854; B. pelagica Stingelin, 1895; B. pellucida Stingelin, 1895; and B. similis (Sars, 1890). The primary differences between the species are the shape and length of the trunk (antenna I and rostrum grown together) and shell spine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation